Prenatal Carbamazepine Exposure and Academic Performance in Adolescents: A Population-Based Cohort Study. (14th February 2023) - Ren, Tai; Lee, Priscilla Ming Yi; Li, Fei; Li, Jiong
Abstract : Background and Objectives: To investigate whether children born to mothers who used carbamazepine during pregnancy had worse academic performance in adolescence. Methods: This population-based cohort study included all live-born singletons in Denmark between 1996 and 2002 who participated in the national ninth-grade exit examination (n = 370, 859). Those born to mothers with prescription of antiseizure medications other than carbamazepine during pregnancy were excluded. We examined the association of in utero exposure to maternal carbamazepine redeemed during pregnancy (n = 290) with academic performance of offspring, defined by the scores in Danish and mathematics in ninth-grade exit examination. We estimated mean z-score difference with linear regression adjusted for socioeconomic factors and potential indications, including epilepsy and medication for other psychiatric disorders. Additional analyses addressing confounding by indication included comparison between in utero exposed vs past exposed and between past exposed and never exposed. In utero exposure to valproate monotherapy was used as a positive control and in utero exposure to lamotrigine as a negative control. Results: At the age of 16.1 (SD 0.4) years, adolescents in utero exposed to maternal carbamazepine monotherapy had lower scores both in Danish and mathematics in ninth-grade exit examination (adjusted z-score difference, −0.14 [95% CI −0.24 to −0.05] and −0.17 [95% CI −0.28 to −0.07], respectively). In utero exposure to carbamazepine monotherapy was associated with lower scores than past exposure only (adjusted z-score difference, −0.24 [95% CI −0.41 to −0.06] for Danish and −0.25 [95% CI −0.44 to −0.06] for mathematics), while past exposure to carbamazepine was associated with minor decrease in offspring's academic performance (adjusted z-score difference, −0.02 [95% CI −0.09 to 0.06] for Danish and −0.07 [95% CI −0.16 to 0.01] for mathematics). The association was also observed for in utero exposure to valproate monotherapy, but not for in utero exposure to lamotrigine. Discussion: In utero exposure to carbamazepine was associated with poorer academic performance in adolescence, as represented by lower scores in ninth-grade exit examination in Danish and mathematics. Additional studies are needed to confirm these findings because of limitations in this study and variable findings in prior studies. Classification of Evidence: This study provides Class III evidence that academic performance, as reflected in ninth-grade exit examinations in Danish and mathematics, was worse among those exposed to carbamazepine monotherapy in utero, compared with those without in utero exposure to antiseizure medications.